A Case Report of a Successful Percutaneous Trial and Surgical Placement of a Spinal Cord Stimulator in a Patient With Severe Thoracolumbar Scoliosis. Issue 9 (July 2020) - Cheng, Jenny Zhao; Bao, Mike H.; Shen, Shiqian
Abstract : Spinal cord stimulation has been demonstrated as a therapeutic option for patients with persistent lumbar radicular pain secondary to failed back surgery syndrome. This case report demonstrates a successful percutaneous spinal cord stimulator (SCS) trial followed by surgical placement of a permanent SCS to treat lumbar radicular pain and axial low back pain in a patient with severe thoracolumbar scoliosis status after laminectomy and spinal fusion surgery. Currently, there is a paucity of literature on this topic.